Digital Human Modeling in the Occupational Safety and Health Process: An Application in Manufacturing. Issue 2 (3rd April 2018) - Schall Jr., Mark C.; Fethke, Nathan B.; Roemig, Victoria
OCCUPATIONAL APPLICATIONS: Digital human modeling and simulation software has been identified as an effective tool for evaluating work tasks and design alternatives without requiring the expense of physical mock-ups and production trials. Despite recent commercial advancements and a broader availability of digital human modeling platforms, the peer-reviewed scientific literature lacks sufficient demonstration of the application of digital human modeling software within an occupational safety and health process for mitigating exposures to physical risk factors in a real-work environment. We describe the implementation of a commercially available digital human modeling platform as a component of an occupational safety and health process in a manufacturing environment over the course of 1 year. Success stories, challenges, and practical recommendations are discussed.